Adenoid ‘ameloblastoma: Clinicopathological description of 4 additional BRAF-negative cases - CİNEL, ZELİHA LEYLA (My University, 2023)
Objective: Adenoid ameloblastoma (AA) is an epithelial odontogenic tumor that was recognized as a separate entity in the last odontogenic classification of WHO in 2022. The etiology is unknown, and the pathogenesis remains controversial. The objective of this study is to contribute the clinicopathological features of 4 additional BRAF-negative cases to the existing literature, aiming to enhance the molecular understanding of this unique tumor in the forthcoming classification. Materials and methods: This study consists of a case series of four patients diagnosed with AA. The patients’ demographic and clinical information were collected from the universities’ medical achieves. Histopathologically, all cases were reexamined according to the latest update of the WHO odontogenic tumor classification. In addition to H&E and immunohistochemical stains, cytogenetics was also evaluated. Results: Well-defined unilocular radiolucent lesions were observed in all cases. Ameloblastoma-like components exhibited reserved nuclear polarity, suprabasal stellate reticulum-like epithelium, duct-like structure, whorls/morules, and cribriform architecture were common features. Variable immunoreactivity to CK7, CK19, CK14, p63, and p40 were determined, and proliferative activity was greater than 15%. The BRAF molecular study revealed no mutations. Conclusions: When diagnosing AA, the essential histopathological characteristics must be rigorously applied, and a significant portion of the lesion should contain these features. Additionally, despite limited molecular data, since the BRAF mutation commonly observed in ameloblastomas is not present in the majority of AA cases, we propose changing the term \"ameloblastoma\" to \"ameloblastic\" and referring to it as \"adenoid ameloblastic tumor\" in the forthcoming classification.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Diş Hekimliği; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; DENTISTRY, ORAL SURGERY & MEDICINE; OTORHINOLARYNGOLOGY; Cerrahi; Ağız Cerrahisi; Surgery; Oral Surgery; Otorhinolaryngology; Adenoid ameloblastoma; BRAF p.V600E; Odontogenic tumor; WHO